EVALUASI PROGRAM UJIAN NASIONAL (UN) PADA SMK NEGERI DI JAKARTA SELATAN - Henry Eryanto; Marsofiyati Marsofiyati; Darma Rika Swaramarinda (Jurnal Ilmiah Econosains, 2016)
ABSTRACT This study aims to determine Evaluation Program of the National Examination (UN) in the State Vocational School in South Jakarta. This study includes qualitative research, where research in SMK who has the Office Administration Program in South Jakarta, which contained 10 SMKN. The resources are empirically Principal and Chairman of the Program Office Administration. Collecting data using the method of observation, interviews, documentation and archive footage, while the analysis of data using qualitative data analysis interactive model. The results showed that: (1) Implementation of UN 2015 went well, although there are still obstacles to the program, but this is normal and can be controlled quickly and well. (2) The 2015 UN Program is a pilot program, where this year the UN goal is to assess the achievement of national competency standards on a particular subject. (3) The results of the UN as a basis for mapping the quality of programs and or education units, consideration of selection into the next level of education and training as well as providing assistance to the education unit in its efforts to improve the quality of education, not as a determinant of graduation of students. (4) each learner formal education and non-formal education pathways equality eligible for the national exam and has the right to repeat the extent not otherwise meet the criteria of achievement of competence of graduates, and every student must attend one national exam at no charge. Keywords: Evaluation Program, National Exam